4.2x+9=3(1.2x+4)

Simple and best practice solution for 4.2x+9=3(1.2x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4.2x+9=3(1.2x+4) equation:



4.2x+9=3(1.2x+4)
We move all terms to the left:
4.2x+9-(3(1.2x+4))=0
We calculate terms in parentheses: -(3(1.2x+4)), so:
3(1.2x+4)
We multiply parentheses
3x+12
Back to the equation:
-(3x+12)
We get rid of parentheses
4.2x-3x-12+9=0
We add all the numbers together, and all the variables
1.2x-3=0
We move all terms containing x to the left, all other terms to the right
1.2x=3
x=3/1.2
x=2+0.6/1.2

See similar equations:

| x/5=36/4 | | y+2/3=2y+4/2 | | 375=80x | | 0.1x-0.8x-62=1 | | 4x+2x-5=x+35 | | 375=40x | | 3a=B=225 | | )3+4x-8-2x=3x+7 | | 350=14x | | 4x=7+ | | 15=3.14x | | 2x-3÷4+6=-1 | | 0.8x+x=198 | | -98+28x+6x^2=0 | | 28=28n-7n^2 | | x^2-2x+4=67 | | 7n^2+28n-28=0 | | 3x+7=2x-8-6x | | 12−x=8 | | 7n^2-28n-28=0 | | 6x^2+28x-98=0 | | 7k^2+3k=0 | | 1.8x=168 | | 1.6x=160 | | 36-12y=-30-45y | | 2x–86=2x–86 | | x–50=2x–86 | | 20n+12=12n+24 | | 13y-26=y+28 | | —17=2x—3 | | 2(x+5)=69x+1) | | 12x-18=-3x-3 |

Equations solver categories